1995
DOI: 10.1073/pnas.92.14.6274
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of csk inhibits acid-induced activation of NHE-3.

Abstract: Opossum kidney OKP cells express an apical membrane Na+/H+ antiporter that is encoded by NHE-3 (for Na+/H+ exchanger 3) and is similar in many respects to the renal proximal tubule apical membrane Na+/H+ antiporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 37 publications
(38 reference statements)
2
39
0
1
Order By: Relevance
“…Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6]. There is a growing awareness that tyrosine phosphorylation cycles are critical in regulating NHE activities in a number of cell types [6][7][8][9][10], as has also been shown for ERK [11]. Other studies have demonstrated that NHE and ERK activities are modulated by overlapping upstream enzymes, including phosphoinositide 3h-kinase (PI-3K), phospholipase Cγ, and PKC [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6]. There is a growing awareness that tyrosine phosphorylation cycles are critical in regulating NHE activities in a number of cell types [6][7][8][9][10], as has also been shown for ERK [11]. Other studies have demonstrated that NHE and ERK activities are modulated by overlapping upstream enzymes, including phosphoinositide 3h-kinase (PI-3K), phospholipase Cγ, and PKC [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse embryos lacking csk exhibit increased c-Src, Fyn, and Lyn activity and increased levels of tyrosine protein phosphorylation (38). Overexpression of wild-type Csk suppresses endogenous c-Src activity (39) and, in opossum kidney cells, blocks acid-induced activation of Na ϩ /H ϩ antiporter, a process associated with p60 c-src activation (40). Fig.…”
Section: C-src In G␤␥ Subunit-mediated Map Kinase Regulationmentioning
confidence: 99%
“…Both Pyk2 and c-Src activation are required for acid to activate NHE3 activity. [59][60][61][62] Downstream from c-Src is endothelin-1 (ET-1) production and ET-1/ETB mediates acid stimulation of NHE3 involving exocytic insertion of NHE3 into the apical membrane. This process requires an intact cytoskeleton, 65 and is associated with NHE3 phosphorylation.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Both Pyk2 and c-Src activation are required for acid to activate NHE3 activity. [59][60][61][62] Downstream from c-Src is endothelin-1 (ET-1) production and secretion by the proximal tubule. 53,63 The mechanism by which c-Src stimulates ET-1 secretion is not yet known.…”
Section: Adaptation To Metabolic Acidosismentioning
confidence: 99%